(untitled) - Silberschatz, Abraham (Boston, 2006)
The fifth edition of Database System Concepts retains the overall style of prior editions while evolving the content and organization to reflect the changes that are occurring in the way databases are designed, managed, and used.
Nguyên lý hệ quản trị cơ sở dữ liệu
Keywords: Database management